Acute and Subchronic Toxicity Study of Euphorbia hirta L. Methanol Extract in Rats - Kwan, Yuet Ping; Ibrahim, Darah; Yeng, Chen; Subramaniam, Sreeramanan; Sreenivasan, Sasidharan (Hindawi Publishing Corporation, 2013)
Despite Euphorbia hirta L. ethnomedicinal benefits, very few studies have described the potential toxicity.The aim of the present study was to evaluate the in vivo toxicity of methanolic extracts of E. hirta.The acute and subchronic oral toxicity of E. hirta was evaluated in Sprague Dawley rats. The extract at a single dose of 5000mg/kg did not produce treatment related signs of toxicity or mortality in any of the animals tested during the 14-day observation period. Therefore, the LD 50 of this plant was estimated to be more than 5000mg/kg. In the repeated dose 90-day oral toxicity study, the administration of 50mg/kg, 250mg/kg, and 1000mg/kg/day of E. hirta extract per body weight revealed no significant difference (